Case Report: Genetic analysis of oculocutaneous albinism type 2 caused by a new mutation in the OCA2 - Luo, Lei; Ma, Min; Yang, Yanzhang; Zhao, Hui (Frontiers in Pediatrics, 2025)
Oculocutaneous albinism (OCA) is a condition inherited in an autosomal recessive manner, leading to reduced pigmentation in the skin, hair, and eyes. Oculocutaneous albinism type 2 (OCA2) is one of the most common forms of OCA, caused by OCA2 mutations. This case report presents a newborn with suspected OCA. Postnatal examination revealed white skin, golden-colored hair, and reduced visibility of the retinal pigmented epithelium on fundus photography. Genomic DNA was extracted from the peripheral blood of the patient and her parents. Whole Exome Sequencing (WES) was conducted using chip capture-based high-throughput sequencing technology to analyze genomic DNA from the proband and her parents. Genetic variants of his parents were identified using sanger sequencing. A mutation in the OCA2 was identified: NM_000275.2: c.863_886delTGAGCAGGACCTTTGAGGTGA (p.Met288_Leu295del). Subsequently genetic analyses were conducted. This mutation was recognized as a potential disease-causing mutation, validating diagnosis of OCA2. Currently, few reports have been published regarding this mutation site. It represents a new mutation site in OCA2 (NM_000275.2:c.863_886del), contributing to the genetic diversity of the OCA2.